Analisis Cuaca Sawah Bekas Tambang Timah di Kabupaten Bangka Berbasis Internet Of Things (IoT) - Budianto, Tri Hendrawan; Wardana, Agung; Kurniawan, Rudy; Syafrudin, Syafrudin; Hartoko, Agus (Telcomatics, 2025)
Unpredictable weather changes in rice field areas have a direct impact on community activities, particularly in the agricultural sector. Weather data from the BMKG (Indonesian Meteorological, Climatological, and Geophysical Agency) is general in nature and not specific to small areas, and there are limitations in real-time monitoring and historical data, which pose their own challenges. This study designed a weather monitoring device based on DHT11 sensors, rain sensors, BMP180, UV, and LDR, which can record data in real-time to an SD card and send information via Telegram bot. This tool successfully identifies weather conditions such as cloudy, mostly cloudy, sunny, and rainy, as well as supporting parameters such as temperature, humidity, air pressure, UV index, and CO₂. The first measurement results showed a 79% dominance of cloudy weather, while the second measurement showed 65% cloudy weather. These findings prove the effectiveness of the device in providing accurate and sustainable local weather data to support decision-making in the agricultural sector.